In vitro perfusion of the whole ovary as a cow in order to model human ovarian cryopreservation whole (Experimental biology, 2015)
Cryopreservation and transplantation of whole ovary with vessels is an effective solution to prevent post-transplant ischemia. In fact, perfusion intact mammalian ovary through the arteries and veins, is the most technically difficult part of the process of cryopreservation. In the first series of experiments, ovary (n = 145) were perfused for 60 minutes and at intervals of 1 to 1.5 hours after removal of the ovaries at the slaughterhouse. In a second series of experiments, (n = 29) was performed with ovarian perfusion rate of 25 ml / hour (0.42 mL / min) for 60 minutes after removal of the ovaries. Relevant technology development prolonged perfusion intact ovaries cryoprotectants at low temperatures, as previously, it was found that 24-hour cooling to 50C before cryopreservation beneficial effect on human ovarian tissue freezing. The purpose of this study was to investigate the effectiveness of perfusion intact bovine ovaries at different rates of perfusion and time elapsed between removal of the ovaries and the beginning of perfusion.
Keywords: cryopreservation; cryoprotectants; ovaries; perfusion; ischemia; anastomosis